Integral inequalities for submanifolds of Hessian manifolds with constant Hessian sectional curvature - Bektas, M.; Yildirim, M. (Shiraz Univ, 2006)
In this paper, we obtain two intrinsic integral inequalities of Hessian manifolds.
Keywords: Hessian manifolds; Hessian sectional curvature